ON SUN-DRYING OF BOMBAY DUCK - PRABHU, P V (Fishery Technology, 2025)
Sun-drying of Bombay duck by hanging on scaffolds gave better products than those obtained by drying them in trays. Optimum rate of drying and quality of dried product were obtained when the fish were suspended at the rate of 50 to 60 per meter length of the rope. The quality of the raw material as affected by the delays in different hauls in the fishing trip was reflected in the dried products also.